CENTRAL ASIAN CULTURE IN THE 17TH-20TH CENTURIES - Zoirova, Maxarram Yoqubovna (Innovative Development in Educational Activities, 2023)
In Central Asia, during the Timurid era, culture became world famous for its classical level. During the Shaibani and Ashtarkhani period (XVI-XVIII centuries), the country experienced complex processes of feudalism. The development of crafts in the 16th century helped to expand transit and internal trade. During this period, there were more than 60 types of crafts. He had diplomatic trade relations with Central Asia, India, Iran, Balkh, Russia, Turkey and other countries. In the 15th and 16th centuries, science developed significantly in Movarounnahr. Literature, history, memorization and visual arts have gone through a specific stage of development.